تقييم أثر التجوية على المباني الأثرية بالقاهرة الفاطمية: دراسة جيومورفولوجية تطبيقية باستخدام نظم المعلومات الجغرافية - القصراوى، محمد عبداللطيف عبدالمطلب (جامعة كفر الشيخ - كلية الآداب, 2022)
تناولت الدراسة تقييم أثر التجوية على المباني الأثرية بالقاهرة الفاطمية، وذلك من منظور جبومورفولوجي تطبيقي، وتناولت الدراسة دور العوامل الطبيعية المؤثرة على عمليات التجوية بالمباني الأثرية بمنطقة الدراسة والتي تمثلت في دراسة خصائص أحجار البناء، والخصائص المناخية، والزلازل، بالإضافة إلى تأثير العوامل البيولوجية، والمياه الأرضية، كما تناولت الدراسة تأثير العوامل البشرية على عمليات التجوية بالمباني الأثرية وتمثلت في دراسة عمر المبنى، والتلوث الجوي، والتسرب من شبكات المياه والصرف الصحي، بالإضافة إلى دراسة الترميم الخاطئ، والسلوكيات الخاطئة في التعامل مع المباني الأثرية، ومن خلال التقييم الميداني لأثر التجوية على المباني الأثرية بالمنطقة، وتطبيق نماذج موثقة لتصنيف خطرها خلصت الدراسة إلى أن خطر التجوية يتدرج من الدرجة المتوسطة إلى المتوسطة للشديدة، ثم الشديدة فالشديدة جدا، وأضافت الدراسة التوصيات اللازمة لضرورة استفادة صناع القرار والمتخصصين من نتائج الدراسة، وكيفية الحد من أخطار التجوية التي تتعرض لها المباني الأثرية وسبل مواجهتها، وأهمية معاملة القاهرة الفاطمية كمنطقة تراث خالية من كافة أنواع التعديات على المباني الأثرية. The study dealt with assessment the impact of weathering on the archaeological buildings in Fatimid Cairo, from an applied geomorphological view, The study dealt with the role of natural factors affecting weathering processes in the archaeological buildings in the study area, which was represented in studying the characteristics of building stones, climatic characteristics, and earthquakes, in addition to the influence of biological factors and ground water, and The study also dealt with the impact of human factors on weathering processes in archaeological buildings, and it was represented in studying the age of the building, air pollution, and leakage from water and sewage networks, in addition to studying the wrong restoration, and wrong behaviors in dealing with archaeological buildings, through the field assessment of the impact of weathering on the archaeological buildings in the study area, and the application of documented models to classify its danger, the study concluded that the risk of weathering ranges from medium to moderate severe, then severe to very severe, and the study added the necessary recommendations for the need for decision-makers and specialists to benefit from the results of the study, and how to reduce From the dangers of weathering to which archaeological buildings are exposed, and the treatment of Fatimid Cairo as a heritage area free from all kinds of encroachments on archaeological buildings.
Keywords: المباني الأثرية -- العمارة الإسلامية -- الخصائص المناخية -- عمليات التجوية